Effectiveness of Law Enforcement on Corporate Bankruptcy Status - Siregar, Benito (Global Legal Review, 2024)
This study aims to evaluate the effectiveness of law enforcement on the status of bankruptcy in Indonesia. Lawrence M. Friedman's legal system theory is used because it has a comprehensive scope to evaluate the effectiveness of enforcing legislation. This study uses juridical-normative research with statutory and case approach. The laws and regulations studied are Law no. 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations (KPKPU), while the case study takes the case of the bankruptcy of Telkomsel in 2012. This study finds that bankruptcy law enforcement in Indonesia has not been effective. This is because Indonesian bankruptcy law still has weaknesses in terms of substance, structure, and legal culture. In addition, this study finds that the fundamental weakness of Law no. 37 of 2004 is the application of simple proof as a mechanism for imposing bankruptcy statements to debtors. The application of this simple evidence makes law enforcers (judges) tend to ignore facts other than the two conditions stipulated in Law no. 37 of 2004 to impose bankruptcy status, namely the existence of two or more creditors and the existence of one debt that is due and collectible. In the end, the simple evidence mechanism does not open up opportunities for law enforcement officials to assess the debtor's ability to pay off their debts.